ANALISIS KETEPATAN METODE SPRINGATE DAN FULMER DALAM MEMPREDIKSI KEBANGKRUTAN PADA PERUSAHAAN SUBSEKTOR PARIWISATA, RESTORAN, DAN HOTEL DI INDONESIA - Lisa Alfarizi; Zainal Zawir Simon; Andri Gunawan (Lembaga Penelitian Universitas YARSI, 2024)
The present investigation used the Springate and Fulmer methodologies to ascertain the bankruptcy rate of companies in the tourism, restaurant, and hotel industries that are listed on the Indonesia Stock Exchange (IDX) between 2017 and 2021. It is intended to be examined closely. The secondary data used in this study was gathered from the websites and financial statements of the companies listed in IDX. The Kolmogorov-Smirnov test, independent samples t-test, and inferential statistics were the data analysis methods employed. With an accuracy of 84 percent, Fulmer's method was found to be the most effective in forecasting bankruptcy, followed by his Springate method at 20 percent, according to the study's findings. We recommend that more researchers employ different bankruptcy procedures, look at businesses in diverse industries, and lengthen the study term